INFORMATION CULTURE: A NEW APPROACH - Nodirbek Kodirov Mamasoliyevich (Scholar Express Journal, 2023)
The article provides a socio-philosophical analysis of the processes associated with the formation of information culture in young people. Based on the fact that in today's era of globalization, the formation of an information culture among young people is an important factor in maintaining the spirituality of the nation, conclusions and recommendations have been developed
Keywords: information; education; information culture; social development